Symptomatic posttreatment edema after stereotactic radiotherapy (SRS/FSRS) for intracranial meningiomas: patterns and predictive factors - Dorra Aissaoui; Naoual Oulmoudne; Houda Bahig; Giuseppina Laura Masucci; Robert Moumdjian; David Roberge; Cynthia Menard; Laurent Létourneau-Guillon; Carole Lambert; Jean-Paul Bahary (Clinical and Translational Radiation Oncology)
Background: Symptomatic posttreatment edema (SPTE) is a complication that may develop after radiotherapy for intracranial meningiomas. Our study aims at reviewing rates of SPTE in a large cohort of a single institution and identifying possible predictive factors. Methods: We retrospectively analyzed data of 293 patients with 304 intracranial meningiomas irradiated at our institution between 2005 and 2018. We evaluated rates of SPTE and investigated numerous factors by univariate and multivariate analysis. Kaplan Meier analysis was used for estimation of actuarial local control and overall survival. Results: Median age was 60 years. Meningiomas were treated with fractionated stereotactic radiation therapy (70 %), single fraction stereotactic radiosurgery (24 %) or fractionated stereotactic radiosurgery (6 %). Median imaging follow-up was 60 months, actuarial 10 year local control rate for patients with grade 1 meningiomas who received radiotherapy as definitive treatment was 99 %. Local control at 5 years was 94 % for grade 1 meningioma, 57 % and 53 % for grade 2 and 3 respectively. Sixteen patients (5.5 %) developed SPTE, median time to onset was 3 months (range 1–26 months). the higher rates of SPTE observed were in midline (13 %) and convexity (9 %), compared to skull base tumors (2 %). On univariate analysis, age > 60 years (p > 0.03), pretreatment peritumoral edema (p = 0.014), medline location (p = 0.018), tumor size > 30 mm (p = 0.015) and grade 2 histology (p = 0.03) were predictive of SPTE. On multivariate analysis, only tumor location and size remained statistically significant. Conclusions: Based on our results, patients at high risk of SPTE can be identified based on patient and tumor characteristics. The best treatment technique in high risk patients is yet to be defined.